KONSERVATISME AKUNTANSI DAN KEPERCAYAAN INVESTOR - Tanti Anita (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2017)
This research intended to test the influence of accounting conservatism explanations such as contracting, litigation, taxation, and regulation to investor trust. In this case, the indicator of the investor trust can be seen from the stock return. A number of manufacturing companies registered in Indonesia stock exchange from year 2008 to 2012 was used as samples in this research. The test of the influence of accounting conservatism explanations to stock return has been done by using double regression analysis. Based on the result of the test, the accounting conservatism explanations for contracting, litigation and regulation has no significant influence to stock return. On the contrary, it has positively significant influence to taxation.